Correlation between signal input and output in PctA and PctB amino acid chemoreceptor of Pseudomonas aeruginosa. Issue 3 (4th March 2015) - Reyes‐Darias, José A.; Yang, Yiling; Sourjik, Victor; Krell, Tino
Summary The PctA and PctB chemoreceptors of Pseudomonas aeruginosa mediate chemotaxis toward amino acids. A general feature of signal transduction processes is that a signal input is converted into an output. We have generated chimeras combining the Tar signaling domain with either the PctA or PctB ligand binding domain (LBD). Escherichia coli harboring either PctA‐Tar or PctB‐Tar mediated chemotaxis toward amino acids. The responses of both chimeras were determined using fluorescence resonance energy transfer, and the derived EC50 values are a measure of output. PctA‐Tar and PctB‐Tar responded to 19 and 11 L‐amino acids respectively. The EC50 values of PctA‐Tar responses differed by more than three orders of magnitude, whereas PctB‐Tar responded preferentially to L‐Gln. The comparison of amino acid binding constants and the corresponding EC50 values for both receptors revealed statistically significant correlations between inputs and outputs. PctA and PctB possess a double PDC (PhoQ‐DcuS‐CitA) LBD – a family of binding domain found in various other amino acid chemoreceptors. Similarly, various chemoreceptors share the preferential response to certain amino acids (e.g. L‐Cys, L‐Ser and L‐Thr) that we observed for PctA. Defining the specific inputs and outputs of these chemoreceptors is an important step toward better understanding of their physiological role.